The Effect of Special Exercises Using an Apparatus for Teaching Volleyball Spike in Players Aged 10 – 12 Years Old - Abedullah, Alaa; Tariq, Zyiad (Journal of Physical Education, 2017)
The importance of the research lies in using modern apparatus for teachingvolleyball players. The problem of the research was the lack of apparatuses and tools forteaching volleyball skills a matter that led the researcher to design an apparatus for teachingspiking in volleyball. The researcher used the experimental method. The subjects were (12)novice volleyball players aged 10 – 12 years old from the national center for gifted athletesin volleyball. The subjects were equally divided into the controlling group and theexperimental group. The data was collected and treated using proper statistical operations toconclude that the special exercise used with this apparatus have a positive effect on the speedof learning spike in volleyba